An Observational Study to Assess Samprapti Ghataka in Cervical Spondylosis with Special Reference to Radiological Findings (AYUSHDHARA, 2021)
The western lifestyle, characterized by convenience food, television and PC’s taking its all on children as well as adults and is producing increased number of overweight, passive youngsters with lifestyle diseases. Spondylosis is degenerative inter vertebral disc with secondary proliferative osteoarthritis. Disc spaces collapse and associated ligament thickening and bony proliferation result in nerve root compression and narrowing of spinal canal. Cervical spondylosis which is a degenerative disorder in which structural and also functional derangements take place. It is an age related and also work-related disability usually found in the 30-60 years of age group. According to Ayurveda it is one among the Vataja Nanatmaja Vikara. There is no exact clinical entity mentioned in classics like cervical spondylosis, but it can be compared to Greevastambha, Apabahuka, Vishwachi Manyastamba, Manyagraha, Shirograham, Greevahundanam, Greevasandhigatavata. Cervical Spondylosis also known as cervical osteoarthritis or neck arthritis, is a common age-related condition that affects the joints and discs in our neck.